Pengaruh Risiko Kredit,Risiko Pasar dan Risiko Likuiditas Terhadap Efisiensi Operasional Bank Konvensional di Indonesia Periode 2022-2024 - Silvani Silvani; Siti Raihana Pudjiomo; Nilam Zulma; Musdalifa Musdalifa; Septian Dwi Cahyu (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2026)
This study is motivated by the importance of risk management in maintaining the operational efficiency of conventional banks in Indonesia amid economic dynamics that may increase credit risk, market risk, and liquidity risk. The study aims to examine the effects of credit risk, market risk, and liquidity risk on the operational efficiency of conventional banks listed on the Indonesia Stock Exchange during the 2022–2024 period. A quantitative approach with a causal associative research design was employed. The sample consisted of 40 banks selected using purposive sampling, resulting in 110 observations. Secondary data from annual financial reports were analyzed using panel data regression with EViews 13 through the Chow, Hausman, and Lagrange Multiplier tests. The results indicate that the Fixed Effect Model (FEM) is the most appropriate model. Partially, credit risk measured by Non-Performing Loans (NPL) and liquidity risk measured by the Loan to Deposit Ratio (LDR) have a significant effect on operational efficiency, while market risk measured by the Net Interest Margin (NIM) has no significant effect. Simultaneously, the three independent variables significantly affect operational efficiency, with an Adjusted R² of 85.41%. The study concludes that effective credit risk and liquidity risk management play an important role in improving the operational efficiency of conventional banks.